The Public Participation And Sustainable Development Perspective On Zero Waste Policy In Mataram City, Ntb Province - Rahmadani; Ashari; Raodah, Putri (Unram Law Review, 2023)
This research aims to confirm that public participation has been accommodated and actualized in the policy and the implementation of the zero-waste policy in Mataram City from a sustainable development perspective. The particular purpose of this research is to identify the involvement of the community, viewed through public participation and sustainable development indicators, in the policy and its implementation of the Zero Waste policy, which can be used as correction and evaluation for related stakeholders. The method used in this research is the normative-empirical research method, which incorporates normative legal elements supported by additional data or empirical elements. The approaches adopted were conceptual, statutory approaches, and observation of facts in the field. The types of data employed include primary data (in the form of observation of data or facts in the field) and secondary data, consisting of primary legal materials, that is, a regional regulation related to the Zero Waste Policy. Data collection techniques were literature studies and field studies, and then the data were analyzed using qualitative methods and presented descriptively.